Limitations of stabilizing effects of fundamentalists: Facing positive feedback traders - Michael Heinrich Baumann; Michaela Baumann; Alexander Erler (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The authors analyze financial interactions between chartists with bounded leverage and fundamentalists within a heterogeneous agent model, focusing on the role of fundamentalists to stabilize prices. While many related studies are solely based on simulations, the authors analytically prove that the existence of fundamentalists is insufficient to avoid asset price bubbles for a certain setup of a feedback trader model. Moreover, similar studies very often face the criticism that chartists might run out of money before the emergence of bubbles, as these studies typically analyze the role of chartists with unbounded leverage. In the work at hand, however, the authors prove that even in an environment where chartists have limited access to finance, their investment behavior can lead to exploding prices. The chartists under study are so-called positive feedback traders, whose leverage is bounded. Additionally, the authors derive upper boundaries for positive feedback traders' initial investment necessary to avoid exploding prices. In order to stabilize stock/asset markets, intervention measures might be helpful.
Keywords: D84; G01; G11; 330; heterogeneous agents; feedback trading; fundamentalists; chartists; trend followers; financial bubbles; financial crisis